A Follow-up Study of the Effectiveness of Health Education Program by Applying the Brain Based Learning to Promote Cervical Cancer Screening among Women Risk Group - มานะยิ่ง ชาลินี; บางนิ่มน้อย มะลิวัลย์; สีกุด ภูนรินทร์ (Primary Health Care Journal (Northeastern Edition), 2021)
This study is quasi experimental research used one-group repeated measures design and aimed to study a follow-up study of the effectiveness of health education program by applying the brain based learning for promote cervical cancer screening among women risk group. The samples were 39 chosen from the women risk groups through purposive sampling as well as the verification against the eligibility criteria. The samples were engaged in 10-week health education program-oriented activities on a weekly basis. Subsequently 3, 6, and 7 months after the activities had ended, the researchers conducted the follow-up and evaluation sessions of behavioral continuity through a questionnaire. Descriptive data were analyzed by descriptive statistic including frequency, percentage, mean and standard deviation. Comparative analysis was used Independent t-test, which the difference is found of 95% confidence interval (95%CI), One-way repeated measures analysis of variance and pairwise comparisons. The research results revealed that health education program-oriented activities showed that the mean scores achieved 3 and 6 months after the activities had ended were significantly different (P-value < 0.001). The mean scores of cervical cancer, perceived benefits and perceived barriers of cervical cancer screening program and admission to cervical cancer screening service tended to increase.